Differential proteome response to H5N1 highly pathogenic avian influenza (HPAI) viruses infection in duck - Ye, Yu; Fan, Huiying; Li, Qi; Zhang, Zhen; Miao, Peisi; Zhu, Jun; Liu, Jie; Zhang, Jie; Liao, Ming (Frontiers in Immunology, 2022)
Ducks and wild aquatic birds are the natural reservoirs of avian influenza viruses. However, the host proteome response that causes disease in vivo by the H5N1 HPAI virus is still unclear. This study presented a comprehensive analysis of the proteome response in Muscovy duck lung tissue during 3 days of infection with either a highly virulent DK383 or an avirulent DK212. An unbiased strategy- isobaric tags for relative and absolute quantitation (iTRAQ) in conjunction with high-performance liquid chromatography with tandem mass spectrometry (HPLC-MS/MS) was utilized to investigate the infection mechanism. Pathways derived from analysis of 292 significantly altered proteins may contribute to the high pathogenic nature and disease progression of H5N1 viruses. Global proteome profiles indicated improved correlation with the virus titers and gene expression patterns between the two strains of the H5N1 virus. DK383 replicated more efficiently and induced a stronger response specific to severe disease. While proteins involved in the immune response of neutrophils were increased markedly by DK383, DK212 evoked a distinct response characterized by an increase in proteins involved in the maturation of dendritic cells, adhesion of phagocytes, and immune response of macrophages. The differentially activated Akt/mTOR/p70S6K pathway might involve in the host response to H5N1 viruses. Therefore, systematically integrated with datasets from primary genomic and virus titer results, proteomic analyses may help reveal the potential pathogenesis.